Increasing Tourist Satisfaction Through Service Quality: The Mediating Role of Memorable Tourism Experience - Eviana, Nova (Yayasan Sinergi Kawula Muda, 2024)
In the tourism sector, tourist satisfaction is the primary determinant for assessing the effectiveness of managing tourism destinations and the long-term viability of tourism enterprises. Tourist satisfaction becomes crucial to discern the influential factors that impact the tourist's satisfaction. This research seeks to elucidate the direct effect of service quality on tourist satisfaction and its indirect effect mediated through memorable travel experiences. This study employed a quantitative research design, utilizing cross-sectional surveys with questionnaire instruments. The validity and reliability of the questionnaire instrument were assessed through a sample of 30 respondents. A total of 204 tourists, selected using an accidental sampling technique, participated in research conducted in Jakarta Old Town. The collected data was subjected to Structural Equation Modeling (SEM PLS). The findings from the tests reveal that service quality exerts a direct and significantly positive impact on tourist satisfaction, and it also exerts an indirect influence mediated through the creation of memorable travel experiences. Hence, it is imperative for the management of Jakarta Old Town to consistently enhance the quality of services to cultivate memorable tourism experiences. These remarkable travel experiences foster an emotional bond that can instigate the development of contentment and other favorable behaviors.